Keefektifan Pelayanan Online dan Dewata E-KTP di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Trenggalek - Hafid Barka Amrullah; Rahdian Subakti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The Corona Virus Disease (Covid-19) pandemic has had a significant impact on various affected countries. The pandemic also has an impact on public services such as the E-KTP program. Electronic KTP (E-KTP) is a population document that contains a security system in the form of administration and information technology. The E-KTP program carried out by the government aims to replace the old KTP as a form of service to the entire community. Even though there is a policy of limiting public services, public service providers are still obligated to comply with minimum service standards by taking into account the rights and obligations of each part. To meet this target, the Department of Population and Civil Registration of Trenggalek Regency issued a new policy in the form of DEWATA services (layanan desa/kelurahan wajib tertib adminduk) for the Trenggalek community. The purpose of this article is to determine the effectiveness of DEWATA services. The research method is literature study. With this DEWATA service, the population management process can continue and maintain the implementation of health agreements.